Two new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from South America - Lima, Lucas R. C.; Molineri, Carlos; Pinheiro, Ulisses; Salles, Frederico F. (Zootaxa, 2016)
Caenis Stephens, 1835 is a relatively diverse South American genus of Caenidae (Ephemeroptera), with 22 recorded species, but much of its diversity remains poorly explored in this region. In the present study, two new species of Caenis with apically pointed forceps are described: Caenis amacayacu sp. nov., based on male adults from Colombia; and C. elidioi sp. nov, based on all life stages from several localities in Brazil.